2017
DOI: 10.2134/agronj2016.04.0196
|View full text |Cite
|
Sign up to set email alerts
|

Multicollinearity in Path Analysis: A Simple Method to Reduce Its Effects

Abstract: The multicollinearity in path analysis was investigated in different scenarios. A biometrical approach identified the multicollinearity‐generating traits. Data derived from averages overestimated the correlation coefficients. The use of all sampled observations increased the accuracy in path analysis. A simple sample tracking method that reduces multicollinearity is proposed. Some data arrangement methods often used may mask correlation coefficients among explanatory traits, increasing multicollinearity in mul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
58
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 64 publications
(63 citation statements)
references
References 38 publications
3
58
0
2
Order By: Relevance
“…Using the EFA, it was possible to determine how many factors exist (in other words, in how many latent variables the original set of variables could be reduced), the relationship between the factors and how the variables were associated with these factors (Ullman, 2006). Finally, the estimation of final factor scores allowed dealing with the multicollinearity, a systemic issue in multivariate analyses (Olivoto et al, 2017), incorporating in the new first latent variables the original structure of the data, thus leading to dimensional reduction.…”
Section: Discussionmentioning
confidence: 99%
“…Using the EFA, it was possible to determine how many factors exist (in other words, in how many latent variables the original set of variables could be reduced), the relationship between the factors and how the variables were associated with these factors (Ullman, 2006). Finally, the estimation of final factor scores allowed dealing with the multicollinearity, a systemic issue in multivariate analyses (Olivoto et al, 2017), incorporating in the new first latent variables the original structure of the data, thus leading to dimensional reduction.…”
Section: Discussionmentioning
confidence: 99%
“…To proceed with the path analysis, the multicollinearity of the correlation matrix among the 14-explanatory traits (put here the explanatory traits) was initially diagnosed by the condition number (CN), given by the ratio between the largest and smallest eigenvalues of explanatory traits correlation matrix. We decided to exclude the variables causing severe multicollinearity problems from the analysis, as suggested by Olivoto et al (2017). After solving possible problems with multicollinearity, a phenotypic path analysis was performed considering GY as the dependent trait and those variables that remained after multicollinearity adjustment as explanatory traits.…”
Section: Discussionmentioning
confidence: 99%
“…When evaluating the multicollinearity of the phenotypic correlation matrix among the explanatory traits, we observed severe multicollinearity effects caused by the traits SL, SW, TGW, FGC, SHL, RL. Thus, these traits were removed from path analysis to circumvent the harmful effects of multicollinearity (Olivoto et al, 2017).…”
Section: Cause and Effect Relationshipsmentioning
confidence: 99%
“…To better understand the factors affecting the correlations between variables, Wright (1921) proposed a method called path analysis, which deconstructs the simple correlations between direct and indirect effects of independent variables on the dependent variable. This method was originally used in plants by Dewey and Lu (1959), and was subsequently applied in the context of various agricultural crops (OLIVOTO et al, 2017). However, forested areas are rarely studied (RESENDE et al, 2016) and no researches are found in the Brazilian literature available for modeling forest biomass.…”
Section: Introductionmentioning
confidence: 99%
“…In the prediction of direct and indirect effects of a set of variables on the dependent variable, it is necessary to estimate the path coefficients that are obtained by linear regression, in which the variables were previously standardized (OLIVOTO et al, 2017). The estimate of coefficients can be adversely influenced by the multicollinearity effects among the variables involved.…”
Section: Introductionmentioning
confidence: 99%